WELL CASING DESIGN FOR PLAN OF XXX GEOTHERMAL FIELD DEVELOPMENT - SYARIF HIDAYATULLAH (NIM : 22608004); Pembimbing : Dr-Ing. Bonar Tua Halomoan Marbun, DENI
Geothermal field development will go through drilling stage to make a connection between subsurface to the surface. The connection would result to the deliverability of thermal fluid in the earth to be exploited for electricity generating in a Geothermal Power Plant system. At this drilling stage, casing design has a significant effect for performance and life time of a geothermal well. Casing design in the drilling of geothermal wells should consider the conditions commonly found in a geothermal systems. Geothermal well casing design is very different from the design of oil and gas wells for geothermal reservoir has a very high temperature. But the temperature factor is still not considered in the design of a geothermal well casing. The temperature will reduce the strength of the casing so that the design requires a correction factor. Correction factor added to the design of the casing is usually calculated in oil and gas well drilling. Casing yield strength calculation caused by fluid production during production phase is also conducted in this final project. Analysis of the casing load during production caused by erosion, corrosion and temperature tension as a basis for selecting higher yield strength, thicker and smoother casing wall. Casing selection based on load during the production sould be additional consideration in the design of geothermal wells casing.